2020
DOI: 10.4018/ijmbl.2020010104
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Conceptual Framework Highlighting Mobile Learning Challenges

Abstract: Over the last decade, there has been much interest in mobile technologies in teaching and learning as emerging and innovative tools. Despite this focus, mobile learning (m-Learning) implementation is facing many challenges. This study presents a tentative conceptual framework that consolidates existing research related to mobile learning implementation barriers. The study adopted a systematic review of the literature on challenges to mobile learning. A total of 125 papers published between 2007 and 2017 were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…SARITHA App also has the advantage that, the use of learning applications is not limited by space and time. This is reinforced by Benali and Ally [33] who explain that application use is not bound by place and time. Learning activities can be carried out anywhere, anytime and anything [34].…”
Section: B Discussionmentioning
confidence: 96%
“…SARITHA App also has the advantage that, the use of learning applications is not limited by space and time. This is reinforced by Benali and Ally [33] who explain that application use is not bound by place and time. Learning activities can be carried out anywhere, anytime and anything [34].…”
Section: B Discussionmentioning
confidence: 96%
“…However, interactive science learning media created only for particular material and questions in the application cannot be added and updated. Benali & Ally (2020) also developed Android-based software in the research to produce mobile phone-based learning media. Still, the developed application is only compatible with the operation of the froyo version of the Android system.…”
Section: Introductionmentioning
confidence: 99%
“…There are different trends for the development and implementation of ICT in education, and in particular, mobile learning is gaining strength in recent years, due to the massification of mobile devices in the population (Gómez & Badia, 2016). Interest in these mobile technologies as emerging and innovative tools has grown in the last decade (Benali & Ally, 2020) and involves, in general terms, "the integration of mobile devices in teaching and learning" (Grant, 2019, p. 1).…”
Section: Introductionmentioning
confidence: 99%
“…In systematic reviews of trends in mobile learning research, its potential to aid in education is shown (e.g., Bano et al, 2018;Diacopoulos & Crompton, 2020;Lai, 2019;Liu et al, 2021;Yildiz et al, 2020), as well as its main challenges (Benali & Ally, 2020). In Crompton and Burke (2020), it was reported that 46% of the time mobile devices are used to replicate activities that can be performed without technology.…”
Section: Introductionmentioning
confidence: 99%